If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19c + 3d + -6c + 8d = 0 Reorder the terms: 19c + -6c + 3d + 8d = 0 Combine like terms: 19c + -6c = 13c 13c + 3d + 8d = 0 Combine like terms: 3d + 8d = 11d 13c + 11d = 0 Solving 13c + 11d = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-11d' to each side of the equation. 13c + 11d + -11d = 0 + -11d Combine like terms: 11d + -11d = 0 13c + 0 = 0 + -11d 13c = 0 + -11d Remove the zero: 13c = -11d Divide each side by '13'. c = -0.8461538462d Simplifying c = -0.8461538462d
| 3(x+3)=6-14(x+5) | | 5y+y=5y+7 | | -a+5a=-53 | | 19x-6x=26 | | 9(x-3)+9=9x-17 | | 8x-1+5x+90=180 | | 25x^8/5x= | | 9=-3/8y | | 4/5w=-24 | | 42=-7/3y | | 0.14x+0.07(6000-x)=518 | | 53x-17-9x=18+44x-35 | | 53x-179x=18+44x-35 | | y=3x^2-15x-12 | | -5=x^2+4x | | 6x^6+6x-24= | | 2-4[4-(2y-5)]= | | 5000=(x+50)x | | 6x-3=(-4x+3) | | xb-6=cx+4 | | K/3-18=-26 | | 5*-5*25-5= | | 15x-10=6x-(x+2)+(3-x) | | -16x^2+78x+6=0 | | bx-6=cx+4 | | -8=3/7x | | h+2(h-6)=18 | | 10x+4y+5z=170 | | 4(x+3)=6(2x-5) | | -7/4c=-7 | | F(7)-f(4)/7-4 | | -18=2/3x |